Students’ perceptions of some factors influencing academic achievement at a rural South African university - Sikhwari, T.D.; Ravhuhali, F.; Lavhelani, N.P.; Pataka, F.H. (South African Journal of Higher Education, 2019)
Research has shown that a major challenge facing higher education institutions in South Africa is the success of students in their studies. The long-term plan to increase the participation rate in higher education in South Africa highlights the need for universities to investigate the factors that influence students’ success. The present study explored participants’ perceptions of factors influencing academic excellence achievement. A qualitative design was used. Data were collected by means of a questionnaire with open-ended questions. The ten respondents (5 males and 5 females) for the study were conveniently selected from a historically black institution of higher learning in South Africa. The data were analyzed through content analysis. The results indicate that students’ academic achievements are influenced by various factors, such as self-motivation, self-discipline, peer support, and lecturers’ teaching approaches.